Modeling the energy management system taking into account the load characteristics and economic performance - Mosatafaei Afra (ՀՀ ԳԱԱ հրատ.)
Electrical load management (ELM)[3] is one of the most basic and most important branches of demand side management (DSM)[3] . Energy management in the proposed system is carried out by load management. Load management techniques divided into three main categories - load shading, valley filling and load shifting.Պահանջարկի կառավարման տեսանկյունից ամենահիմնականը և կարևորը բեռի էլեկտրական կառավարումն է: Առաջարկվող համակարգում կառավարումը էներգասնուցման ասպարեզում իրականացվում է բեռի կառավարմամբ: Բեռի կառավարման մեթոդները ներկայանում են երեք հիմնական դասերով՝ բեռի անջատում, տարածքում բեռի բաշխում, բեռի փոխանջատում: Электрическое управление нагрузкой (ELM) является одним из основных и наиболее важных для управления спросов (DSM). В предлагаемой системе менеджмент в энерго-питании осуществляет управление нагрузкой. Методы управления нагрузкой разделяются на три основные категории - затенение нагрузки, распределение нагрузки по территории и переключение нагрузки.
Keywords: Technology